2016
DOI: 10.1002/art.39820
|View full text |Cite|
|
Sign up to set email alerts
|

The Regulatory B Cell Compartment Expands Transiently During Childhood and Is Contracted in Children With Autoimmunity

Abstract: Objective Regulatory B cells that inhibit immune responses through interleukin-10 (IL-10) secretion (B10 cells) have been characterized in adults with autoimmune disease. This study examines B10 cells across the entire age range of normal human development, and their changes during pediatric autoimmunity. Methods The phenotype and numbers of blood B10 cells were examined in healthy individuals and children with autoimmunity by flow cytometry. B10 cell function was assessed by measuring the effect of B cell-d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 54 publications
2
12
0
Order By: Relevance
“…11 In humans, B10 cells of peripheral blood are increased in childhood (8-10 years-old) and are low in adults. 12 Interestingly, B10 cells are very low in advanced age where they exhibit a negative correlation with serum levels of rheumatoid factor; 13 a finding that is in line with the concept that deficiency of Breg cells likely contributes to loss of immunological tolerance and the development of autoimmunity. Breg cells are very low in peripheral blood and have to be increased in order to be studied.…”
Section: Regulatory B Cellssupporting
confidence: 53%
“…11 In humans, B10 cells of peripheral blood are increased in childhood (8-10 years-old) and are low in adults. 12 Interestingly, B10 cells are very low in advanced age where they exhibit a negative correlation with serum levels of rheumatoid factor; 13 a finding that is in line with the concept that deficiency of Breg cells likely contributes to loss of immunological tolerance and the development of autoimmunity. Breg cells are very low in peripheral blood and have to be increased in order to be studied.…”
Section: Regulatory B Cellssupporting
confidence: 53%
“…We next investigated whether there was an intrinsic IL-10 defect in patient B cells using the CD40–CD40L interaction which is key for B cell development and induces IL-10 in B cells ( 80 ) Contrary to Kalampokis et al, who reported a reduction in Breg IL-10 in JDM patients ( 81 ), we did not observe a difference in JDM patients pre-treatment and controls with the CD40L stimulus, indicating that patient B cells can produce IL-10 with CD40 activation. These results suggest that activation through CD40 is not defective in these patients.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, B cells also act to suppress immune responses. Accumulating studies have revealed that an immunoregulatory subset of B cells exists and exerts multifaceted functions (7)(8)(9)(10). In the 1970s, a suppressive subset of B cells was firstly hypothesized to exist and modulate immune responses, based on reports indicating that the depletion of B cells in splenocytes was correlated with increased severity and duration of delayed-type hypersensitivity in a guinea pig model (11,12).…”
Section: Introductionmentioning
confidence: 99%